The students' critical thinking skills through creative teaching - Musazay, Asma M. Saber
The lack of critical thinking in the current world is an issue of great concern to educators. As the educators perceived the importance of this issue, they ask themselves whether teaching critical thinking is a viable possibility that can be implemented in the teaching process. This study is aimed to look at teacher's creativity in teaching critical thinking and how it helped students in creating a community of inquiry among themselves. It also investigated the challenges as well as the advantages/ disadvantages of teaching critical thinking. This multiple case study explores qualitatively, the sequence of creative teaching and the enhancement of critical thinking skills in children through two different creative teaching approaches the stand-alone and the infused methods. Data were collected via observation, interviews of both teachers and students as well as content analysis. The study was conducted in Malaysia and observed two different classes; one from the International Islamic School in Gombak using the Hikmah Pedagogy; and the other from the Saudi Arabian School in Kuala Lumpur, embedding critical thinking in their mathematics class. The two classes were observed, and their teachers interviewed while two students from each class were also interviewed. The results revealed that although teachers used different methods in enhancing students' critical thinking, their method concur with all the steps in teaching critical thinking as mentioned by Duron, Limbach and Waugh's. The steps emphasise what the students should know, participations through questioning, practice what was assessed, review, refine and adjust and finally providing feedback and assessment of learning. It was also found that the students reach different levels of intellectual standards, elements of reasoning and intellectual traits, which characterise their critical thinking process. Students in the stand-alone class seemed to exhibit more of the characteristics, due to the nature of the subject. The challenges in teaching critical thinking are student's shyness and their unwillingness to speak, the difficulty in evaluating the enhancement of critical thinking and the time constraint that requires the teacher to complete all the objectives of the lesson. Among the advantages in teaching for critical thinking are the social and academic progress of the students and the experience teachers gain from applying creatively critical thinking in their lessons. The disadvantages include the time that is given in the lesson is not entirely enough to see a complete enhancement of performance among all students. Through this research, suggestions and implications were proposed to improve the teaching methods and how to overcome the challenges that were faced during the lessons. This study proposed that critical thinking should be taught throughout the students' academic career and not for a certain period of time for successful and long lasting results that could be applied locally and internationally. Based on the findings, the case studies displayed positive outcomes for each of the schools that implemented both teaching methods, leading to a development of the critical thinking skills and cultivate the culture of enquiry through critical thinking. In other words, mastering the art of questioning and carrying a meaningful discussion, consistency and choosing suitable stimulus material or anchor problems are important factors in focusing on building and sharpening the child's critical thinking. It is hoped that through these recommendations, systems are developed to enable children to nurture and enhance their ability to express their thoughts creatively and critically within their uniqueness and individuality.